The development of cognitive abilities following the new outcomes of psychological theories - Blumen, Sheyla (1997)
The most representative models of cognitive development following the new outcomes of psychological theories are presented. Then a brief analysis of the models in terms of six factors related to different areas in psychology and social sciences (importance of each stage, processes, knowledge, individual differences, context and limits in the cognitive development) is developed. Finally, an integration of the model developed by Sincoff and Sternberg (1989) is presented.